Validity of student evaluation of teaching in higher education: a systematic review - Quansah, Frank; Cobbinah, Andrews; Asamoah-Gyimah, Kenneth; Hagan, John Elvis (Frontiers in Education, 2024)
Data obtained from students regarding the quality of teaching are used by higher education administrators to inform decisions concerning tenure, promotion, course development and instructional modifications, among others. This article provides a review regarding studies conducted to examine the validity of student evaluation of teaching, specifically focusing on the following objectives: (1) identify the context where studies have been conducted on student evaluation of teaching; (2) find out the methodologies usually employed for assessing the validity of student evaluation of teaching; and (3) establish the sources of measurement error in student evaluation of teaching. The systematic review was conducted based on the PRISMA checklist. The databases searched include Scopus, Web of Science (WoS), and Google Scholar using some specific keywords. After applying the four eligibility criteria, 15 papers were left to be analyzed. Major themes discussed were the settings where more studies have been conducted, methods mostly adopted by scholars in the area, and the sources of measurement errors and validity issues. It was concluded that students were found at the centre of inconsistencies in the evaluation process. The study recommended that further studies should closely study the behaviours of students during the evaluation exercise.